Relationship Of Family Knowledge And Support With Pregnant Women's Compliance In Consuming Fe Tablets In The Working Area Of Publich Health Center Poleang Utara - Yulli Fety; Lisnawati Lisnawati; Arfan (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2025)
Introduction:Fe consumption coverage figures in Indonesia have not yet reached the target, including at the North Poleang Health Center, Bombana Regency, Southeast Sulawesi Province, which only reached 12%. Objectives:This study aims to determine the relationship between knowledge and family support and pregnant women's compliance with consuming FE tablets Methods:This research is a quantitative research with a cross-sectional design. The population in this study was 117 people with a sample size of 30 people selected using proportional sampling techniques. Results:The test used was the Chi Square test. The results of the Chi-square statistical test carried out obtained a value of Xhit>Xtab 0.621>3.84. The hypothesis was rejected, based on the assessment criteria, there was no relationship between knowledge and compliance of pregnant women in consuming Fe tablets. Furthermore, the results of the test for the closeness of the relationship showed that the value of φ was 0.471 or showed a moderate relationship. As well as a value of 10,541>3,841, the hypothesis is accepted, based on the assessment criteria, there is a relationship between family support and the compliance of pregnant women in consuming Fe tablets. Furthermore, the results of the relationship strength test show that the φ value is 0.593 or shows a strong relationship. Conclusions: The conclusion of this study is that knowledge hevent corre;ation with maternal compliance and family support have a relationship with maternal compliance in consuming Fe tablets.